Identification of a Novel Astrovirus in Pinnipeds - Zhang, Peijun; Su, Haoxiang; Peng, Ruoyan; Chan, Jasper Fuk-Woo; Bai, Shijie; Wang, Gaoyu; Huang, Yi; Hu, Xiaoyuan; Luo, Jun; Liu, Sisi; Li, Youyou; Xue, Liying; et al. (Frontiers in Microbiology, 2022)
Astroviruses infect human and animals and cause diarrhea, fever, and vomiting. In severe cases, these infections may be fatal in infants and juvenile animals. Previous evidence showed that humans in contact with infected animals can develop serological responses to astroviruses. Mamastrovirus 11 is a species of Mamastrovirus and was first reported in 2018. It was detected in the fecal samples of a California sea lion. The genome sequence of its capsid protein (CP) was submitted to GenBank. However, the genome sequence of its non-structural protein region was not elucidated. In the present study, we characterized the genome sequences of the novel astroviruses AstroV-HMU-1 and AstroV-like-HMU-2. These were obtained from California sea lions (Zalophus californianus) and walruses (Odobenus rosmarus) presenting with loose stools. A phylogenetic analysis revealed that the CP of AstroV-HMU-1 closely clustered with Mamastrovirus 11 while its RNA-dependent RNA polymerase (RdRp) and serine protease (SP) were closely related to the mink astrovirus in the genus Mamastrovirus. The genome of AstroV-HMU-1 provided basic information regarding the NS protein regions of Mamastrovirus 11. Recombination analyses showed that the genomes of Z. californianus AstroV-HMU-1, VA2/human and the mink astrovirus may have recombined long ago. The NS of AstroV-like-HMU-2 segregated from the Astroviridae in the deep root of the phylogenetic tree and exhibited 36% amino acid identity with other mamastroviruses. Thus, AstroV-like-HMU-2 was proposed as a member of a new genus in the unclassified Astroviridae. The present study suggested that that the loose stools of pinnipeds may be the result of occasional infection by this novel astrovirus. This discovery provides a scientific basis for future investigations into other animal-borne infectious diseases.